Human topoisomerase inhibition and DNA/BSA binding of Ru(II)-SCAR complexes as potential anticancer candidates for oral application - De Grandis, Rone A. [UNESP]; Camargo, Mariana S. de; Silva, Monize M. da; Lopes, Erica O. [UNESP]; Padilha, Elias C. [UNESP]; Resende, Flavia A.; Peccinini, Rosangela G. [UNESP]; Pavan, Fernando R. [UNESP]; Desideri, Alessandro; Batista, Alzir A.; Varanda, Eliana A. [UNESP] (Springer, 2017)
Three ruthenium(II) phosphine/diimine/picolinate complexes were selected aimed at investigating anticancer activity against several cancer cell lines and the capacity of inhibiting the supercoiled DNA relaxation mediated by human topoisomerase IB (Top 1). The structure-lipophilicity relationship in membrane permeability using the Caco-2 cells have also been evaluated in this study. SCAR 5 was found to present 45 times more cytotoxicity against breast cancer cell when compared to cisplatin. SCAR 4 and 5 were both found to be capable of inhibiting the supercoiled DNA relaxation mediated by Top 1. Interaction studies showed that SCAR 4 and 5 can bind to DNA through electrostatic interactions while SCAR 6 is able to bind covalently to DNA. The complexes SCAR were found to interact differently with bovine serum albumin (BSA) suggesting hydrophobic interactions with albumin. The permeability of all complexes was seen to be dependent on their lipophilicity. SCAR 4 and 5 exhibited high membrane permeability (P-app > 10 x 10(-6) cm.s(-1)) in the presence of BSA. The complexes may pass through Caco-2 monolayer via passive diffusion mechanism and our results suggest that lipophilicity and interaction with BSA may influence the complexes permeation. In conclusion, we demonstrated that complexes have powerful pharmacological activity, with different results for each complex depending on the combination of their ligands.
Keywords: Anticancer agent; Ruthenium(II) complexes; Topoisomerase; Binding affinity; Caco-2 permeability